At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

The work of a student to solve the equation 4(2x − 4) = 8 + 2x + 8 is shown below:

Step 1: 4(2x − 4) = 8 + 2x + 8
Step 2: 6x − 8 = 16 + 2x
Step 3: 6x − 2x = 16 + 8
Step 4: 4x = 24
Step 5: x = 6

In which step did the student first make an error and what is the correct step?

A). Step 2; 8x − 4 = 2(6 + x + 6)

B). Step 2; 8x − 16 = 16 + 2x

C). Step 3; 6x − 2x = 16 − 8

D). Step 3; 6x + 2x = 16 + 8


Sagot :

Answer:

B

Step-by-step explanation:

He added 4 to 2 instead of multiplying.

Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.